(untitled) (Eureka Journal of Education & Learning Technologies, 2026)
In the context of rapid socio-economic development and labor market transformation, introducing students and youth to the world of professions has become one of the key tasks of the modern education system. This process requires not only the efforts of educational institutions but also close cooperation with social partners. In this regard, the integration of the neighborhood community and the school plays a significant role in organizing effective career guidance activities.